The Native Yucca: a Boon to the Farmers of the Arid North-east Mexico - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Bio-resource and Stress Management, 2011)
Growing naturally in the arid and semi-arid zones of Mexico and the United States Yucca serves as an important source of fibers for inhabitants of this region. Besides, its flowers and fruits are also consumed by the local people. Flowers are also used as feed for livestock. However, over-exploitation of this natural resource poses a threat to the desert eco-system and subsistence of inhabitants of arid lands. This paper provides an insight into the distribution, ecology, morphology, reproduction, growth, method of fiber extraction and processing, etc. of Yucca with future areas of research for effective conservation and management of this valuable slow-growing natural resource.